Representation of The Meaning of The Song “Sampai Jadi Debu” By Ananda Badudu - Safitri, Laura Haris; Marwan, Iwan (Faculty of Tarbiyah, Institut Agama Islam Negeri (IAIN) Kediri, Indonesia, 2024)
This research aims to determine the meaning of the connotation and denotation meaning of a song entitled